'Caution, we have power': Resisting the 'school-to-sweatshop pipeline' through participatory artistic praxes and critical care. Issue 5 (4th July 2019) - Cahill, Caitlin; Alberto Quijada Cerecer, David; Reyna Rivarola, Alonso R.; Hernández Zamudio, José; Alvarez Gutiérrez, Leticia
ABSTRACT: How might participatory creative praxes make visible a politics of critical care and new imaginaries for resisting the 'school-to-sweatshop pipeline'? Drawing upon arts-based participatory action research processes led by the urgent concerns of young people of color based in Salt Lake City, Utah, we consider the role of cultural production in providing a social and shared context for rearticulating undocumented students' everyday experiences negotiating the 'production of illegality' and racialized exclusions in school. Attending to participatory creative praxis, we explore how the collective act of art-making generates possibilities to forge solidarities through 'cariño conscientizado', a critically conscious care praxis that seeks to dismantle structural injustices. We conclude raising questions about collective creative praxis as acts of resistance and refusal that take seriously the agency of communities to spark justice for ourselves.